Identifikasi Kerusakan Pada Landing Gear Pesawat Cessna C208B - Sri Mulyani; Harliyus Agustian; Iqbal Dwi Anugerah Pulungan (Universitas Muhammadiyah Yogyakarta, 2024)
One type of aircraft commonly used for flight training, patrol, and transportation in remote areas is the Cessna. It should be understood that each tool and component in the aircraft has its own level of importance and can experience failures in carrying out its functions. These failures often become a problem for users due to a limited understanding of the aircraft engine field. Issues arising from the aircraft's landing gear sometimes involve minor problems that do Does not require a high level of expertise. To solve this, it may be possible for someone with knowledge of landing gear to address the issue. By using the Case-Based Reasoning (CBR) method for fault identification, a technician's expertise in aircraft landing gear can be applied and integrated. The search for solutions or fault identification Can be obtained promptly In the testing results of the Fault System for Cessna C208B Aircraft Landing Gear using the CBR method, the system's calculations were consistent with the manual. However, the application still has some shortcomings in the system, such as the preprocessing stage, which has not been able to search for the root words in a question sentence.